AN INFLUENCE OF USER EXPERIENCE AND BRAND EXPERIENCE ON THE CUSTOMER SATISFACTION AT DISNEY+ HOTSTAR DIGITAL STREAMING SERVICES - Firsan Nova; Putri Elma Fitria (Jurnal Apresiasi Ekonomi, 2023)
Nowadays, we have entered the era of digitalization 4.0 which makes the internet play a very important role in supporting and facilitating humans in their daily activities through a variety of existing technologies. The problems identified were several poor ratings accompanied by complaints submitted by Dinsey+ Hotstar customers regarding the use of the application and there was a lot of competition among Video On Demand (VOD) which caused an unstable subscription rate in Q4 2020 until Q1 2022. This study objectives to examine the influence of User Experience and Brand Experience on Customer Satisfaction at Disney+ Hotstar digital streaming services in Bekasi City. This study applied a causal research type by a quantitative approach. The final was 100 which were rounded off from the results of the calculation of Slovin's formula, and also with conditions met, i.e., at least three times in 1 month final. The data analysis technique uses a multivariate approach with a regression technique. The results of empirical research after the alternate hypothesis test was carried out on User Experience and Brand Experience to Customer Satisfaction resulted in research findings that stated a significant influence on Disney+ Hotstar Customers as partially and simultaneously.